(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Drug safety has become one of the central priorities of public health systems worldwide, as the globalization of pharmaceutical manufacturing, distribution, and trade has multiplied the pathways through which unsafe, substandard, or falsified medicines can reach patients. This article examines the current state of global drug safety practice, including international regulatory harmonization efforts led by the World Health Organization (WHO) and the International Council for Harmonisation (ICH), national pharmacovigilance systems, good manufacturing and distribution practices, and the ongoing struggle against substandard and falsified medical products. Particular attention is given to the role of digital technologies, artificial intelligence, and track-and-trace systems in modernizing adverse-event monitoring and supply-chain security. The article concludes with an assessment of prospective directions for strengthening drug safety, including deeper international cooperation, capacity building in low- and middle-income countries, and the harmonization of regulatory standards. The analysis is intended to be useful for pharmacy students, practicing pharmacists, and regulatory professionals seeking a concise overview of global drug safety practice and its future trajectory.